2017
DOI: 10.1186/s13014-017-0781-4
|View full text |Cite
|
Sign up to set email alerts
|

Real-time in vivo rectal wall dosimetry using MOSkin detectors during linac based stereotactic radiotherapy with rectal displacement

Abstract: BackgroundMOSFET dosimetry is a method that has been used to measure in-vivo doses during brachytherapy treatments and during linac based radiotherapy treatment. Rectal displacement devices (RDDs) allow for safe dose escalation for prostate cancer treatment. This study used dual MOSkin detectors to assess real-time in vivo rectal wall dose in patients with an RDD in place during a high dose prostate stereotactic body radiation therapy (SBRT) boost trial.MethodsThe PROMETHEUS study commenced in 2014 and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Quality assurance can be automated and performed in real time, reducing the learning curve within centers and clinical networks. Technical sub-studies have validated the real time SBRT radiation dose delivery and treatment accuracy (24, 25). We have shown that a protocol incorporating rectal displacement devices, MRI fusion, margin reduction coupled with intrafraction image guidance and homogenous urethral dosing is associated with a low risk of significant urinary and rectal toxicity with a median follow-up of 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…Quality assurance can be automated and performed in real time, reducing the learning curve within centers and clinical networks. Technical sub-studies have validated the real time SBRT radiation dose delivery and treatment accuracy (24, 25). We have shown that a protocol incorporating rectal displacement devices, MRI fusion, margin reduction coupled with intrafraction image guidance and homogenous urethral dosing is associated with a low risk of significant urinary and rectal toxicity with a median follow-up of 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…The next 10 patients will have planning performed on sCT and confirmed on planning CT. Subsequent patients will omit a planning CT, be planned on sCT and have confirmation of accurate dosimetry on treatment using a centrally approved approach, for example, Electronic Portal Imaging Device (EPID) dosimetry38 or in vivo dosimetry 39…”
Section: Methodsmentioning
confidence: 99%
“…MOSFETs and diode-based devices have been utilized for clinical real-time in vivo dosimetry [10][11][12] owning to their good sensitivity, small size, and real-time readout capabilities. However, MOSFETs are expensive, incident angle-dependent, and of limited durability.…”
Section: Introductionmentioning
confidence: 99%